Diagnostic value of the patellar tendon-lateral trochlear ridge distance and the patellar tendon-trochlear groove angle in differentiating lateral patellar instability from malalignment-induced patellofemoral pain - Pacala, Razvan; Schmidt, Sebastian; Dennis, Elizabeth R.; Pahapill, Natalie K.; Zimmermann, Felix; Balcarek, Peter (Knee surgery, sports traumatology, arthroscopy, 2025)
Purpose To compare the patellar tendon-lateral trochlear ridge (PT-LTR) distance and patellar tendon-trochlear groove angle (PT-TGA) between patients with lateral patellar instability (LPI) and those with malalignment-induced patellofemoral pain (PFP), and to evaluate their differential diagnostic validity. Methods Sixty patients with LPI (mean age: 24.2 ± 7.1 years) and 60 patients with malalignment-induced PFP (mean age: 25.3 ± 6.2 years) were included. PT-LTR, PT-TGA, as defined by Dai et al. (PT-TGA1) and Hinckel et al. (PT-TGA2), and additional patellofemoral alignment parameters—including the tibial tubercle-trochlear groove (TT-TG) distance, tibial tubercle-posterior cruciate ligament (TT-PCL) distance, lateral trochlear inclination (LTI) angle, patellar height, valgus deviation, femoral and tibial torsion, knee rotation and leg axis—were measured. The unpaired t tests with Welch's correction, receiver operating characteristic (ROC) curve analysis via the Youden index, and parametric power analysis were utilized. Results PT-LTR, PT-TGA1 and PT-TGA2 values were significantly greater in LPI patients compared to those with PFP (PT-LTR: 8.8 ± 6.7 mm vs. 3.9 ± 5.3 mm; PT-TGA1: 29.1 ± 11.3° vs. 17.3 ± 8.9°; PT-TGA2: 35 ± 9.6° vs. 24.9 ± 8.5°; all p < 0.0001). ROC analysis revealed AUCs of 0.73 (PT-LTR), 0.79 (PT-TGA1) and 0.78 (PT-TGA2). PT-TGA1 demonstrated the highest sensitivity (85%), whereas PT-TGA2 showed the highest specificity (83%). Significant differences were also found for LTI (p < 0.0001), patellar height (p < 0.0001), TT-PCL (p < 0.0001) and valgus deviation (p = 0.004), but not for TT-TG, femur/tibia torsion, or knee rotation. Power analysis confirmed robust statistical validity (Z ≈ 5.60; power = 99.987%). Conclusions While PT-LTR and PT-TGA measurements were significantly greater in patients with LPIs than in those with malalignment-induced PFP, only PT-TGA measurements demonstrated sufficient diagnostic accuracy to identify LPI. The results reinforce the conceptual advantage of angular over linear measurements of the extensor apparatus. Level of Evidence Level III, diagnostic cohort study.